Moderate exercise with a dietary vitamin C and E combination protects against streptozotocin-induced oxidative damage to the kidney and lens in pregnant rats - Simsek, M; Naziroglu, M; Erdinç, A (Georg Thieme Verlag Kg, 2005)
Moderate exercise and vitamin C and E (VCE) supplementation can be beneficial to diabetes due to reducing free radical production in lens and kidney of diabetic pregnant rats. We investigated the effect of VCE supplementation and moderate exercise on lipid peroxidation (MDA) and scavenging enzyme activity in the kidneys and lens of STZ-induced diabetic pregnant rats. Fifty female Wistar rats were used and were randomly divided into five groups. First and second were used as the control and pregnant control group. Third group was the pregnant diabetic group. The fourth group was the diabetic-pregnant-exercise group. VCE-supplemented feed was given to pregnant-diabetic-exercise rats constituting the fifth group. Animals in the exercised groups were moderately exercised daily on a treadmill (16.1 m/min, 45 min/d) for three weeks (five days a week). Diabetes was induced on day zero of the study. Plasma, lens, and kidney samples were taken from all animals on day 20. Exercise and administration of VCE to pregnant diabetic rats resulted in significant decrease in the albumin and total protein values and the elevated MDA, plasma creatinine, and urea levels as an indicator of oxidative stress and renal functional parameters. Exercise and VCE supplementation also increased glutathione peroxidase (GSH-Px), reduced glutathione (GSH), vitamin E, and beta-carotene levels in the kidney, GSH-Px and GSH in the lens, the albumin and total protein values in plasma. In the diabetic pregnant animals, the decreased vitamins A and E concentration and GSH levels in kidney, creatinine, and urea values in plasma did not improve through exercise only although their concentrations were increased by VCE supplementation. Kidney weight did not also affect either by exercise or VCE supplementation. In conclusion, these results suggest that exercise plus VCE affects antioxidant metabolism and reduces lipid peroxidation, thereby improving the damage caused by oxidative stress involved in the pathogenesis of lens and kidney in diabetic pregnant rats. Moderate exercise with dietary VCE may play a role in preventing nephropathy and cataract formation in diabetic pregnant rat.
Keywords: oxidative stress; diabetes; exercise; pregnancy; vitamin C and E